Cryptic Species Discrimination in Western Pine Beetle, Dendroctonus brevicomis LeConte (Curculionidae: Scolytinae), Based on Morphological Characters and Geometric Morphometrics - Osiris Valerio-Mendoza; Jazmín García-Román; Moises Becerril; Francisco Armendáriz-Toledano; Gerardo Cuéllar-Rodríguez; José F. Negrón; Brian T. Sullivan; Gerardo Zúñiga (Insects, 2019)
The western pine beetle (WPB), Dendroctonus brevicomis LeConte, is a major mortality agent of pines in North America. A total of 706 adults of WPB from 81 geographical sites were analyzed with traditional and geometric morphometric methods to evaluate the variation of discrete and quantitative morphological characters with particular attention to the antenna, spermatheca, and seminal rod. Principal coordinates and canonical variate analyses supported three geographical groups in WPB: (1) West, from British Columbia to southern California along the Pacific coast, Idaho, and Montana; (2) East-SMOC, including Nevada, Utah, Colorado, Arizona, New Mexico, Texas, Chihuahua, and Durango; and (3) SMOR, including Coahuila, Nuevo Leon, and Tamaulipas. The pubescence length on the elytral declivity was a robust character for separating West specimens from the other groups. Additionally, the genitalia shape both female and male in dorsal view was a reliable character for discriminating among groups. Based on these results, which agree with genetic and chemical ecology evidence, we herein reinstate Dendroctonus barberi Hopkins (East-SMOC group) and remove it from synonymy with D. brevicomis (West group). Differences in the spermatheca and seminal rod shape of SMOR specimens suggest that these populations might be a different species from D. barberi and D. brevicomis.